Homeotic regulation of segment-specific differences in neuroblast numbers and proliferation in the Drosophila central nervous system. - Prokop, A.; Bray, S.; Harrison, E.; Technau, G.M. (Mechanisms of Development, 1998)
The number and pattern of neuroblasts that initially segregate from the neuroectoderm in the early Drosophila embryo is identical in thoracic and abdominal segments. However, during late embryogenesis differences in the numbers of neuroblasts and in the extent of neuroblast proliferation arise between these regions. We show that the homeotic genes Ultrabithorax and abdominal-A regulate these late differences, and that misexpression of either gene in thoracic neuroblasts after segregation is sufficient to induce abdominal behaviour. However, in wild type embryos we only detect abdominal-A and Ultrabithorax proteins in early neuroblasts. Furthermore, transplantation experiments reveal that segment-specific behaviour is determined prior to neuroblast segregation. Thus, the segment-specific differences in neuroblast behaviour seem to be determined in the early embryo, mediated through the expression of homeotic genes in early neuroblasts, and executed in later programmes controlling neuroblast numbers and proliferation.